The Para diplomacy is an analytical vision in concept and practice: applied models of decentralization governance: international and political journal - Al-Bayati, Prof. Dr. Muhammad Aziz Abdul Hassan (The International and Political Journal, 2025)
Para-diplomacy has come to play an important role in federal governance systems, to be the sub-national actor that exercises multiple roles at both the levels of governance and the exercise of sovereignty. Between this and that, local governments and administrations interact outside their local and regional borders, to begin a new phase in managing foreign partnership policies in service of the states and local regions in any country that follows the federal model. The importance of the research lies in addressing the problem of managing parallel diplomacy (para diplomacy) at the regional, state or other levels, in order to empower new actors inside and outside the sovereign nation-state when sub-national actors seek to exercise complementary roles as far as the exercise of governance and the exercise of sovereignty outside the geographical borders of the countries themselves are concerned, which imposes the necessity of coordination in addressing all problems in managing this type of extended foreign relations only, and the goal of parallel diplomacy lies in managing external files extending beyond the borders of local regional areas, in federal systems of government, which requires searching for effective means and tools capable of managing governance and exercising sovereignty as they are at the core of the jurisdiction of the federal government at the center, provided that the process of understanding the limits of the exercise of powers takes place to avoid any constitutional or administrative problem resulting from the application of the federal system. The research concluded by supporting the research vision of what was proposed by (Panagiotis Soldatos) when he adopted the concept of (para diplomacy) parallel diplomacy in order to manage external powers that are basically classified as central powers of the federal government in federal systems of government and not local governments in the peripheries (Subnational Governments), in order to simplify political work procedures, and proceed with the implementation of development programs at the level of achievement in the states that require political decentralization in sharing power and even exercising sovereignty exclusively, which results in the establishment of subnational governments (Subnational Governments).